2010
DOI: 10.4103/0973-8398.68461
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of ion-exchange resin Indion 204 and Indion 214 for the taste masking of metoclopramide hydrochloride and formulation of rapid-disintegrating tablets

Abstract: T he purpose of this research was to mask the intensely bitter taste of metoclopramide hydrochloride and to formulate a rapid-disintegrating tablet of the taste-masked drug. Taste masking was done by complexing the drug with ion exchange resin, Indion 204 and Indion 214, in different ratios. The complex loading process was optimized for the concentration of resin, swelling time, stirring time, pH, and temperature for maximum drug loading. Drug-resin complexes (DRC) were tested for flow properties, drug content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It was found that upon increasing the processing temperature the entrapment efficiency was significantly (P< 0.05) increased due to increase in the solubility of the drug, the higher temperature tends to increase the diffusion rate of ions by decreasing the thickness of exhaustive exchange zone, as well as increased temperature during complexation increases ionization of drug and resin. [27] , as shown in…”
Section: Effect Of Temperaturementioning
confidence: 77%
“…It was found that upon increasing the processing temperature the entrapment efficiency was significantly (P< 0.05) increased due to increase in the solubility of the drug, the higher temperature tends to increase the diffusion rate of ions by decreasing the thickness of exhaustive exchange zone, as well as increased temperature during complexation increases ionization of drug and resin. [27] , as shown in…”
Section: Effect Of Temperaturementioning
confidence: 77%
“…Differential scanning calorimetry (DSC) was carried out for the characterization of the complex formed. All the DRCs were subjected to DSC and the thermograms were studied for drug-polymer complex formation [13][14][15].…”
Section: Evaluation Of the Prepared Drug-resin Complexes For Drug Relmentioning
confidence: 99%
“…US Patent 5,024,997 describes taste masking of ibuprofen using hydroxypropyl-beta-cyclodextrin in a palatable solution formulation [57] . Taste masked formulations containing IER complexes of ambroxol [58] , ciprofloxacin [59,60] , levofloxacin [61] , metoclopramide [62] , metformin [63] , ondansetron [64] and risperidone [65] was evaluated. US Patent 5,980,882 describes sustained release drugresin complexes of dextromethorphan coated with ethyl cellulose and stabilized by EDTA as a chelating agent [66] .…”
Section: Taste Masking Technologiesmentioning
confidence: 99%